FACTORS AFFECTING ADMINISTRATIVE AND ORGANIZATIONAL SUCCESS IN THE TURKEY'S FORESTRY - Kose, M.; Dasdemir, I; Erol, Yurdakul S.; Yildirim, H-T; Daşdemir, İsmet (Corvinus Univ Budapest, 2019)
This study was dealt with aiming to examine the most important factors (education and self-development, administrative competence, success mentality, motivation and rewarding) affecting administrative and organizational success in the forest resource management of Turkey. For this purpose, four different questionnaires were applied to the total of 565 interviewees related to the forestry section of the Ministry of Forestry and Water Affairs and four different interest groups (employees, subject experts, related institutions and nongovernmental organizations representatives) in nine geographical regions of Turkey. To gather data about the subject and to reach the results, face to face interviews were conducted with interest groups, a questionnaire was applied. The layered-simple random sampling method was used as a sampling method. All obtained data were used as material. The research data were evaluated with descriptive statistics, it was inspected with the Kruskal-Wallis H-Test whether the thoughts of the interviewees related to the most important factors affecting administrative and organizational success differ according to the regions, and the departments, the position and the experience. The different groups were determined by the Duncan Test. Accordingly, most of the interviewees think that the undergraduate education, prevocational and in-service training are inadequate and that they need the most social and economic comprehensive information in the management of forest resources. Middle and upper level managers have the opportunity to further develop themselves, as the duration of experience increases, the administrative competence about forest resources management increases, but scientific studies and research results related to forestry are mostly not followed. The majority of the interviewees correctly identified administrative and organizational success in forestry, determined the most important factors affecting success as organizational and administrative factors and found that there was little or no relationship between success and reward. To increase the success in the forestry, the employees should participate in decisions and the success should be measured and evaluated objectively and numerically in the form of institutional success. According to the results, some suggestions were put forward for development of forest resources management.
Keywords: Forest Resource Management; Education; Administrative Competence; Success Mentality; Motivation And Rewarding; Turkey